2004
DOI: 10.1038/nm1001
|View full text |Cite
|
Sign up to set email alerts
|

Pegylated interferon-α protects type 1 pneumocytes against SARS coronavirus infection in macaques

Abstract: The primary cause of severe acute respiratory syndrome (SARS) is a newly discovered coronavirus. Replication of this SARS coronavirus (SCV) occurs mainly in the lower respiratory tract, and causes diffuse alveolar damage. Lack of understanding of the pathogenesis of SARS has prevented the rational development of a therapy against this disease. Here we show extensive SCV antigen expression in type 1 pneumocytes of experimentally infected cynomolgus macaques (Macaca fascicularis) at 4 d postinfection (d.p.i.), i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

15
332
0
1

Year Published

2005
2005
2013
2013

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 373 publications
(348 citation statements)
references
References 27 publications
15
332
0
1
Order By: Relevance
“…Others (18) demonstrated that IRF-3 dimerization is blocked in SCoV-infected 293 cells, so we think that at least two different mechanisms inhibit IFN-␤ mRNA accumulation in SCoV-infected cells: One suppresses a signaling pathway that activates IRF-3 and the other is the nsp1-mediated promotion of IFN-␤ mRNA degradation. Dual means of inhibiting IFN-␤ mRNA accumulation would seem to be crucial for SCoV to establish infection in the host, because SCoV is known to be susceptible to IFN treatment (19,20).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Others (18) demonstrated that IRF-3 dimerization is blocked in SCoV-infected 293 cells, so we think that at least two different mechanisms inhibit IFN-␤ mRNA accumulation in SCoV-infected cells: One suppresses a signaling pathway that activates IRF-3 and the other is the nsp1-mediated promotion of IFN-␤ mRNA degradation. Dual means of inhibiting IFN-␤ mRNA accumulation would seem to be crucial for SCoV to establish infection in the host, because SCoV is known to be susceptible to IFN treatment (19,20).…”
Section: Discussionmentioning
confidence: 99%
“…SCoV replication in human 293 cells suppresses IFN-␤ mRNA accumulation by inhibiting IFN regulatory factor (IRF)-3 phosphorylation, dimerization, nuclear translocation, and association with CBP͞p300 (18). Because SCoV is susceptible to the antiviral action of IFNs (19,20), inhibition of IFN-␤ transcription appears to be one of SCoV's defenses against host innate immune response. No SCoV gene product(s) is currently known to inhibit IRF-3 function.…”
mentioning
confidence: 99%
“…The basis for continuous deterioration of lung function and the apparent loss of capacity for lung repair after viral load declines is not well understood (33). Clinical studies and in vivo studies with macaque monkeys revealed that the target cells of SARS-CoV infection are primarily type-1 pneumocytes, damage to which is closely associated with the subsequent diffuse alveolar damage (18). Our observations that the pulmonary Oct-4 ϩ colony cells are susceptibility to SARS-CoV infection and allow virus replication leading to their own demise implies a potential role of the pulmonary stem͞ progenitor cells in the apparent loss of capacity for lung repair after SARS-CoV infection and later phases of lung failure.…”
Section: Discussionmentioning
confidence: 99%
“…Although the monkey model mimics to certain degree the clinical course of SARS (16), the mouse model provides the first genetic evidence for angiotensinconverting enzyme 2 (ACE-2) as a crucial SARS-CoV receptor in vivo (17). Although type-1 pneumocytes, and to a lesser extent type-2 pneumocytes, have been shown to be the target cells of SARS-CoV infection in monkey studies (16,18), the identity of mouse bronchiolar epithelial cells infected by SARS-CoV remains unclear (19,20). To investigate the cellular tropism of SARS-CoV in the mouse lung, we set up primary cultures for the enzymereleased cells from lung tissues and attempted to establish pulmonary epithelial cell lines that may enable us to develop a more effective cell-based screening system for chemical inhibitors of virus entry and replication.…”
mentioning
confidence: 99%
“…Of these parameters, relative lung weight and affected lung tissue allowed the best quantitative distinction between the virus groups: they showed clear differences between virus groups from 2 dpi onwards (Table 7), with relatively little within-group variation (Figure 2). These parameters have been used with success before for studies on severe acute respiratory syndrome [18] and on influenza [19]. Immunohistochemistry score for virus antigen expression in the Table 2.…”
Section: Discussionmentioning
confidence: 99%